Epidemiology and clinical management of acute diarrhoea in dogs under primary veterinary care in the UK - Dan G. O’Neill; Lauren J. Prisk; Dave C. Brodbelt; David B. Church; Fergus Allerton (PLoS ONE, 2025)
Background Acute diarrhoea is a common canine veterinary presentation in the UK. This study aimed to report the incidence, demographic risk factors and clinical management for acute diarrhoea diagnosed under primary veterinary care in the UK in 2019. Methods A cohort study design with a cross-sectional analysis was applied to anonymised VetCompass clinical data. Risk factor analysis used multivariable logistic regression modelling. Results The analysis included a random sample of 1,835 confirmed incident acute diarrhoea cases in 2019 from an overall study population of 2,250,417 dogs. After accounting for subsampling, the estimated one-year incidence risk for acute diarrhoea in dogs overall was 8.18% (95% CI: 7.83–8.55). Of the first acute diarrhoea event in 2019 for the 1,835 cases, 1473 (80.27%) had only one physical visit for veterinary care related to the acute diarrhoea. The most common comorbid clinical signs with acute diarrhoea included vomiting (n = 812, 44.25%), reduced appetite (508, 27.68%) and lethargy (444, 24.20%). Overall, 538 (29.32%) cases were recorded as haemorrhagic diarrhoea. The most common clinical managements were probiotics (n = 1094, 59.62%), dietary management (807, 43.98%), antibiosis (701, 38.20%) and maropitant (441, 24.03%). Six breeds showed increased odds of acute diarrhoea compared with crossbred dogs: Maltese (OR 2.17, 95% CI 1.25–3.77), Miniature Poodle (OR 2.17, 95% CI 1.19–3.95), Cavapoo (OR 2.07, 95% CI 1.32–3.25), German Shepherd Dog (OR 1.69, 95% CI 1.29–2.22), Yorkshire Terrier (OR 1.51, 95% CI 1.15–1.98) and Cockapoo (OR 1.36, 95% CI 1.05–1.74). The odds of diagnosis increased in dogs aged under 3 years and dogs aged over 9 years, compared to dogs aged 4–5 years. Conclusions This study confirms acute diarrhoea as a common clinical condition in dogs managed under primary veterinary care, with 1-in-12 dogs diagnosed each year. The identified breed predispositions suggest some genetic element to the condition. The clinical outcomes following veterinary care appear to be very positive, with over 80% of acute diarrhoea cases not receiving a second veterinary visit. However, antibiotic use remained frequent, despite years of recommendation to the contrary and raises concerns about unnecessary antibiotic therapy for this condition.